SAT0128 Clinical features and evolution of pulmonary function in a single-center cohort of patients with rheumatoid arthritis related interstitial lung disease. (15th June 2017) - Rodriguez-García, SC; Castellanos-Moreira, RA; Hernandez-Miguel, MV; Ramirez, J; Cuervo, A; Cañete, J; Sanmarti-Sala, R
Abstract : Background: Interstitial lung disease (ILD) is an extra-articular manifestation of Rheumatoid Arthritis (RA), has been related with a poor prognosis. However, there is a lack of clinical data regarding its evolution with different treatment approaches. Objectives: Our aim was to assess clinical features and evolution of ILD in a cohort of RA patients from a tertiary hospital Methods: Single-centre retrospective observational study including all patients diagnosed with ILD with a previous or posterior diagnosis of RA evaluated from January 2007 to December 2016 in the Rheumatology Department of a university hospital. Variables analysed: age, sex, smoking status, duration of RA, presence and titers of ACPA (antiCCP2) and rheumatoid factor (RF), presence of erosions, use of glucocorticoids (GC), synthetic and biological DMARDs before and after ILD diagnosis and presence of other extra-articular manifestations. We also analysed: duration of ILD, HRCT (High Resolution Computed Tomography) patterns and pulmonary function tests (PFT) at baseline and during follow-up to assess the evolution of the disease. The PFT results were evaluated according to the American Thoracic Society/European Respiratory Society definitions (1). Results: Twenty-one patients (18 women) were included, mean age 68. 4±11.9, mean RA duration 12.3±8.2 years. 9.5% were current smokers and 33.3% former smokers. 61.9% were ACPA + (52.4% with high basal titers, median ACPA titers: 698) and 81% RF+ (47.6% with high basal titers). 71.4% had erosions and 5 patients (23.8%) had extra-articular manifestations, mainly rheumatoid nodules. RA diagnosis was made after that of ILD in 4 patients; mean elapsed time 1.56±1.26 years. In the other 17 patients, the mean duration of RA until ILD diagnosis was 11.2±7.2 years. Currently 17 subjects (85%) receive GC; 4 (19%) in monotherapy and 11 (57.9%) synthetic DMARDs (5 methotrexate, 3 leflunomide (LEF), 1 hydroxychloroquine (HCQ) and 2 with double therapy (HCQ/AZA and HCQ/LEF)). Four patients are currently treated with biological therapy (2 abatacept (ABA), 1 rituximab and 1 etanercept (ETN)), all of them in monotherapy. Five patients received TNFi prior to ILD diagnosis (3 ETN, 1 infliximab and 1 adalimumab). Biological therapy was withdrawn in 3 cases and switched to ABA in the two remaining ones. The median duration of EPID was 2.5 (range 0.7–11.9) years. HRCT patterns were: non-specific interstitial pneumonia (NSIP) 52.9%, usual interstitial pneumonia (UIP) 17.6%, cryptogenic organized pneumonia (COP)11. 8%, and other patterns 17.7%. 14 patients had baseline and follow-up PFT: 9 (64.3%) remained stable; 3 (21.4%) improved and 2 (14.3%) worsened (1 had received previous ETN). There was a trend for worsening of PFT in patients with UIP pattern. No patient died from ILD during this period Conclusions: In our RA-ILD cohort, NSIP was the most common HRCT pattern and PFT remained stable in most patients during follow-up. Five patients (23.8%) had received TNFi prior to ILD diagnosis and only one of them showed worsening of PFT during ETN treatment, with clinical improvement after withdrawal. References: Pellegrino R et al. Eur Respir J. 2005;26:94868. Disclosure of Interest: None declared